Nutritive Value of Edible Meat Powder and Meal from Three Fatty Deep Sea Fishes - Lekshmy Nair, A.; Stephen, Jose; Gopakumar, K. (Fishery Technology, 2025)
Evaluation of the nutritive quality of edible meat powder from Pseneopsis cyanea and of fish meals from Pseneopsis cyanea, Chlorophlhalmus agassizi and Epinnula orienlalis was carried out by chemical and biological methods. Protein efficiency ratio (PER) was lower than or equal to that of the reference protein casein for the meals from P. cyanea and C. agassizi and for the edible meat powder from P. cyanea. The intake of food and PER of E. orienlalis meal was very low. Based on essential amino acid data, leucine, cystine, methionine, hreonine and valine were found to be the limiting amino acids in the meals, the amino acid scores being respectively 78, 85, 72 and 53 for the fish meals from P. cyanea, C. agassizi with and without stick liquor and E. orientalis.